2015
DOI: 10.1371/journal.pone.0125212
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Midregional Proadrenomedullin to Predict Poor Outcome in Patients with Community Acquired Pneumonia

Abstract: Backgroundmidregional proadrenomedullin (MR-proADM) is a prognostic biomarker in patients with community-acquired pneumonia (CAP). We sought to confirm whether MR-proADM added to Pneumonia Severity Index (PSI) improves the potential prognostic value of PSI alone, and tested to what extent this combination could be useful in predicting poor outcome of patients with CAP in an Emergency Department (ED).MethodsConsecutive patients diagnosed with CAP were enrolled in this prospective, single-centre, observational s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Additionally, this marker has been tested mainly as a marker of severity, although there are data indicating that it can be of value in the diagnosis and prognosis of sepsis and bacterial CAP [9]. Once again, it seems highly likely that modifications of this biomarker occur only in very severe bacterial diseases that are relatively uncommon iamong children with CAP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, this marker has been tested mainly as a marker of severity, although there are data indicating that it can be of value in the diagnosis and prognosis of sepsis and bacterial CAP [9]. Once again, it seems highly likely that modifications of this biomarker occur only in very severe bacterial diseases that are relatively uncommon iamong children with CAP.…”
Section: Discussionmentioning
confidence: 99%
“…The detection limit that was calculated using the imprecision profile was previously assessed as being 0.02 ng/mL with a probability of 95% for PCT, 0.05 nmol/L for MR-proADM, and 2.1 pmol/L for MR-proANP. sTREM-1, MR-proADM, MR-proANP and PCT were chosen due to the sensitivity and specificity showed in adults with CAP for differentiating viral and bacterial CAP or severe and non-severe CAP [79]. Clinical and radiographic information, new biomarkers’ serum level determinations and results on nasopharyngeal samples were not available for the central laboratory of the hospital where routine methods were performed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review of 12 studies confirms that an increased MR proADM is associated with increased risk of short term mortality and that a combination of proADM and CURB-65 is associated with an improved predictive efficacy (90). A sizable Swiss study discovered that ProADM was strong predictor of TF including death with an AUC that was significantly higher than that of CRP but similar to PCT (91)(92)(93). Similarly Copeptin has been shown to be a useful marker of early mortality or ICU admission, more so than other biomarkers (89).…”
Section: Novel Biomarkersmentioning
confidence: 90%
“…In addition to clinical risk scores, such as the pneumonia severity index (PSI) [13], several inflammatory and/or cardiovascular blood biomarkers such as white blood cells (WBC), C-reactive protein (CRP), procalcitonin (PCT), pro-adrenomedullin (proADM), as well as pro-atrial natriuretic peptide (proANP) have been found helpful for risk prediction [6,[14][15][16][17][18][19][20]. Particularly, proADM [9,6,[21][22][23][24][25][26][27][28][29][30], proANP [9,6,25,[31][32][33] and PCT [10,22,25,31,[34][35][36] have been associated with risk for shortand long-term all-cause mortality as well as other adverse outcomes, such as severity of illness, admission to the intensive care unit (ICU), and disease-specific complications. Yet, there is insufficient evidence whether these clinical parameters and blood biomarkers are also helpful in predicting more subjective QoL outcomes: mens sana in corpore sano?…”
Section: Introductionmentioning
confidence: 99%